The Dimensions and Paradigms of Multicultural Education and Their Relevance for Islamic Education - Irfan, Muflih Naufal; Haddade, Hasyim; Rusmin, Muhammad; Imam, Muhammad Khoirul (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This study examines the position of multicultural education within the framework of Islamic education by analyzing its key dimensions, paradigms, and conceptual relevance. Although multicultural education has been widely discussed in global scholarship, limited studies have mapped its theoretical constructs while simultaneously linking them to Islamic educational principles in an integrated manner. To address this gap, this study employs a literature review approach that synthesizes classical and contemporary theories of multicultural education, including Banks’ five dimensions and Indonesia’s national multicultural paradigms. The findings show that multicultural education provides a structural and pedagogical foundation through content integration, knowledge construction, prejudice reduction, equity pedagogy, and empowering school culture that aligns with Islamic principles of equality, justice, tolerance, and rahmatan lil-‘ālamīn. The study concludes that integrating multicultural frameworks into Islamic education strengthens its function in shaping inclusive, moderate, and socially responsible learners. This research contributes theoretically by offering a conceptual linkage between two major educational discourses and provides practical implications for developing culturally responsive Islamic education in pluralistic societies.